2014
DOI: 10.14814/phy2.12210
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of cardiovascular circadian rhythms in mice post myocardial infarction: relationship with central angiotensin II receptor expression

Abstract: Angiotensin II (Ang II) is well known to participate in the abnormal autonomic cardiovascular control that occurs during the development of chronic heart failure (CHF). Disrupted cardiovascular circadian rhythm in CHF is also well accepted; however, the mechanisms underlying and the role of central Ang II type 1 receptors (AT1R) and oxidative stress in mediating such changes are not clear. In a post myocardial infarction (MI) CHF mouse model we investigated the circadian rhythm for mean arterial pressure (MAP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Light/dark variations in respiration and arterial pressure appear to be abolished in CHF with reduced ejection fraction. Our study corroborates previous work on blood pressure rhythms in human heart failure patients (Komori et al 2016) and mice with myocardial infarctions (Mousa et al 2014). The current study expands previous findings in showing that CHF also eliminates respiratory circadian rhythms.…”
Section: Discussionsupporting
confidence: 91%
“…Light/dark variations in respiration and arterial pressure appear to be abolished in CHF with reduced ejection fraction. Our study corroborates previous work on blood pressure rhythms in human heart failure patients (Komori et al 2016) and mice with myocardial infarctions (Mousa et al 2014). The current study expands previous findings in showing that CHF also eliminates respiratory circadian rhythms.…”
Section: Discussionsupporting
confidence: 91%
“…Each hour, HR and BP signals were sampled and analyzed [120-s continuous segment (80)], resulting in 12 data points per daytime (12 h) and nighttime (12 h). Daytime and nighttime data were averaged across the 12-h timeframe and displayed with two representative data points per week of the 6-wk study, similar to other analysis methods for long-term telemetry recordings (58,80).…”
Section: Methodsmentioning
confidence: 99%
“…Emerging epidemiological studies have shown correlations between phthalate exposure and human health concerns, including neurological disorders and cardiovascular disease (14,22,32,58,76,78). The latter includes an association between phthalate plasticizer exposure and increased systolic blood pressure (SBP) in adolescents (83,84) and an increased coronary risk in elderly populations (46,60).…”
mentioning
confidence: 99%
“…Blood pressure [2830], vascular remodeling [8, 10, 3133], atherosclerosis [13], cardiac injury [3437], and coagulation [38] are all influenced by circadian clock genes. Thus, this molecular regulator of 24-h rhythmicity controls not only daily and acute pathophysiology, such as blood pressure and thrombosis, but also chronic responses.…”
Section: Discussionmentioning
confidence: 99%